2011
DOI: 10.1073/pnas.1100745108
|View full text |Cite
|
Sign up to set email alerts
|

ADP ribosylation factor 6 (ARF6) controls amyloid precursor protein (APP) processing by mediating the endosomal sorting of BACE1

Abstract: Amyloid β (Aβ) peptides, the primary constituents of senile plaques and a hallmark in Alzheimer's disease pathology, are generated through the sequential cleavage of amyloid precursor protein (APP) by β-site APP cleaving enzyme 1 (BACE1) and γ-secretase. The early endosome is thought to represent a major compartment for APP processing; however, the mechanisms of how BACE1 encounters APP are largely unknown. In contrast to APP internalization, which is clathrin-dependent, we demonstrate that BACE1 is sorted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
234
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(254 citation statements)
references
References 66 publications
19
234
0
1
Order By: Relevance
“…1C, dotted lines), and we also found colocalization in vesicular structures inside the growth cone (arrows). Expression of constitutively active ARF6-Q67L is known to cause enlarged endosomal structures containing ARF6-regulated membrane constituents (Brown et al, 2001;Aikawa and Martin, 2003;Naslavsky et al, 2003;Sannerud et al, 2011). We found that ARF6-Q67L expression generated enlarged endosomal structures that were positive for both ARF6-Q67L and ␤1 integrin throughout adult DRG neurons, including at the cell body (data not shown) and growth cone where vacuolar structures were found aggregating in the central domain (Fig.…”
Section: Does Arf6 Colocalize With Integrin In Axons and Growth Cones?mentioning
confidence: 62%
See 1 more Smart Citation
“…1C, dotted lines), and we also found colocalization in vesicular structures inside the growth cone (arrows). Expression of constitutively active ARF6-Q67L is known to cause enlarged endosomal structures containing ARF6-regulated membrane constituents (Brown et al, 2001;Aikawa and Martin, 2003;Naslavsky et al, 2003;Sannerud et al, 2011). We found that ARF6-Q67L expression generated enlarged endosomal structures that were positive for both ARF6-Q67L and ␤1 integrin throughout adult DRG neurons, including at the cell body (data not shown) and growth cone where vacuolar structures were found aggregating in the central domain (Fig.…”
Section: Does Arf6 Colocalize With Integrin In Axons and Growth Cones?mentioning
confidence: 62%
“…Future work will investigate whether there is a trafficking role for ARF6 in mature CNS axons, or whether it is mainly restricted to the somatodendritic compartment. ARF6 is involved in a number of postsynaptic functions within dendritic spines (Choi et al, 2006;Sakagami et al, 2008;Scholz et al, 2010;Fukaya et al, 2011), and is reported to be largely absent from axons of mature hippocampal neurons in culture (Sannerud et al, 2011); however, it is also reported to function presynaptically (Ashery et al, 1999; Krauss et al, 2003), which might indicate that there is a population of ARF6-positive vesicles trafficking within some adult CNS axons.…”
Section: Integrins Traffic Via Arf6 In Adult Drg Axonsmentioning
confidence: 99%
“…Altered expression has been described previously in patients with AD, Parkinson's, and Huntington's disease [68], as well as animal models of neurodegeneration [69], however, investigation of this cell signaling molecule in the neurodegeneration field is relatively novel. As previously suggested, the changes in mRNA expression of IQSEC1 may not be biologically significant, since there was a small difference in fold change between sham and hypoperfused mice.…”
Section: Discussionmentioning
confidence: 99%
“…11 This is in line with a recent observation of an association of the FRMD4A locus with plasma Aβ1 − 42/Aβ1 − 40, reinforcing the plausibility of the association of FRMD4A with Alzheimer's disease risk and its potential implication in a subtle control of the APP metabolism. 11,12 Thus, FRMD4A polymorphisms are a likely risk factor for Alzheimer's disease. Our data demonstrate that a homozygous null mutation of the same gene causes a severe neurological phenotype with unique dysmorphism.…”
Section: Discussionmentioning
confidence: 99%